STUDIES ON GENETIC VARIABILITY FOR YIELD AND QUALITY CHARACTERS IN RICE (ORYZA SATIVA L.) UNDER INTEGRATED FERTILIZER MANAGEMENT - S. Y. DHURAI; P. K. BHATI; S. K. SAROJ (The Bioscan, 2014)
The analysis of variance revealed significant differences among the genotypes for the all the 9 quantitative and 5 quality traits in rice indicating that enough variability is present in the studied material. The magnitude of difference between PCV and GCV were relatively low for all the traits revealing little influence of the environment in the expression of these traits. The higher magnitude of PCV and GCV was recorded for number of grains per panicle (23.85%; 23.10%) and grain yield per plant (23.17%; 22.04%). All the characters showed high broad sense heritability, while high heritability coupled with high genetic advance as per cent mean was recorded for plant height (97.67%; 30.81%), number of effective tillers per plant (84.10%; 28.19%), panicle length (95.17%; 22.94%), number of grains per panicle (93.79%; 46.08%), kernel elongation ratio (95.81%; 21.88%), kernel length after cooking (99.91%; 23.77%), 1000-grain weight (89.97%;26.22%), harvest index (79.02%; 26.25%) and grain yield per plant (90.48%; 43.20%) indicates the preponderance of additive gene action and such characters could be improved through selection.